Технические требования к высококачественным рельсам для магистральных железных дорог - Рудюк, А. С.; Пыхтин, Я. М.; Иванисенко, Л. И.; Беспоясова, А. С. (НТУ "ХПИ", 2014)
На основании результатов проведенного ранее сравнительного анализа требований европейского стандарта EN 13674-1:2011 "Железные дороги – Путь – Рельсы. Часть 1: Рельсы Виньоля 46 кг/м и более" [1] и российского стандарта ГОСТ Р 51685-2013 "Рельсы железнодорожные. Общие технические условия" [2] и с учетом строительства нового рельсобалочного цеха разработан проект технических условий на высококачественные рельсы для железнодорожных магистральных путей.

Based on results of earlier made comparative analysis of requirements of European standard EN 13677-1:2011 "Railway applications – Track – Rail – Part 1: Vignoles railway rails 46 kg/m and above" [1] and Russian standard GOST R 51685-2013 "Railway rails. General specifications" [2] and taking into account construction of new rail-structural shop one be developed technical requirements for high-quality rails for main railway lines. Developed requirements for rails will be furthered reliability, resource saving during operation and traffic safety for railway transport, widening of rail markets, participation of product manufacturers in worldwide industrial cooperation and attraction of capital investments.
Technical requirements for high-quality rails for main railways
Keywords: рельсы; ресурс наработки тоннажа; качество рельсов; технические требования; механические свойства; железная дорога Украины; железнодорожный транспорт; mechanical properties; chemical composition; rail quality; rails; resource of tonnage operation time